Characterization of TP53 mutations in low‐grade myelodysplastic syndromes and myelodysplastic syndromes with a non‐complex karyotype. (20th October 2017) - Wang, Wei; Routbort, Mark J.; Tang, Zhenya; Ok, Chi Young; Patel, Keyur P.; Daver, Naval; Garcia‐Manero, Guillermo; Medeiros, L. Jeffrey; Wang, Sa A.
Abstract: Objectives: Although commonly associated with high‐grade myelodysplastic syndrome (MDS) and MDS with a complex karyotype, TP53 mutations also occur in low‐grade MDS and MDS with a non‐complex karyotype. In latter cases, their clinicopathological features and the characteristics of TP53 mutations remain poorly characterized. Methods: 176 MDS cases with TP53 mutations were stratified and characterized based on their karyotype and histologic subtype. Results: Among 176 cases, 17% had a non‐complex karyotype and 24% were low‐grade MDS. TP53 mutations often occurred in DNA‐binding domains and the majority of cases had only one mutation, irrespective of their karyotype and MDS subtype. The variant allele frequency (VAF), however, was associated with karyotype complexity and the types of MDS with a lower VAF found in cases with a non‐complex karyotype and low‐grade MDS. A low (<20%) VAF was associated with a better survival, as well as low‐grade subtype. Conclusions: In low‐grade MDS and MDS with a non‐complex karyotype, TP53 mutations showed a lower VAF. Patients with a lower VAF had a better survival. TP53 mutations are not the only prognostic factor in MDS patients with TP53 mutations as the VAF, blast counts and history of prior therapy also play important roles in prognosis.